Brief Report: Power Doppler Ultrasonography for Detection of Increased Vascularity in the Fascia: A Potential Early Diagnostic Tool in Fasciitis of Dermatomyositis. Issue 12 (December 2016) - Yoshida, Ken; Nishioka, Makiko; Matsushima, Satoshi; Joh, Kensuke; Oto, Yosuke; Yoshiga, Masayuki; Otani, Kazuhiro; Ito, Haruyasu; Hirai, Kenichiro; Furuya, Kazuhiro; Ukichi, Taro; Noda, Kentaro; et al.
Abstract : Objective: We previously demonstrated that fasciitis is a common lesion of dermatomyositis (DM) that is detectable early after disease onset by en bloc muscle biopsy combined with magnetic resonance imaging (MRI). Power Doppler ultrasonography (PDUS) is a useful method for detection of inflammation and vascularity in rheumatic diseases. We undertook this study to determine whether fasciitis was detectable by PDUS in patients with DM. Methods: We prospectively evaluated 7 patients with DM and 7 patients with polymyositis (PM) for the detection of fasciitis with PDUS. MRI and PDUS were both performed in all patients. Fasciitis was histologically confirmed by en bloc biopsy. Results: Among all patients with DM, 4 showed signs of fasciitis on MRI, while increased blood flow signals were observed along the fascia by PDUS in 6 DM patients, including 4 patients with early disease (<2 months after the onset of muscle symptoms). Histologically, significant fasciitis was confirmed in 4 patients with DM. In the remaining 3 patients with DM, significant fasciitis was not evident histologically, but mild proliferation of capillaries and mild inflammation were notable in the area of the fascia. Immunohistochemical staining for CD31 indicated abnormal neovascular proliferation in the fascia in patients with DM. None of the PM patients showed signs of fasciitis or increased vascularity by MRI, PDUS, or en bloc biopsy. Conclusion: In our limited population, PDUS was useful for the detection of fasciitis associated with DM, especially in the early stage of disease. The increased blood flow signal as detected by PDUS is involved in angiogenesis accompanying fasciitis in patients with DM.